The Coupling Relationship Between Urbanization and Carbon Emissions From Land Use in Ningxia - Huang, Wei; Li, Jiaxin (Frontiers in Environmental Science, 2022)
To understand the complex relationship between urbanization and carbon emissions, this paper measures the urbanization level and land use carbon emissions of 19 counties and districts in Ningxia from 2009 to 2019 using the integrated index method and carbon emission model, respectively, and explores the coupling relationship based on the coupling coordination degree model, to provide theoretical support for low-carbon urbanization and carbon emission reduction planning in Ningxia. The research results show that (1) The comprehensive evaluation index of Ningxia urbanization system shows a linear increasing trend with an average annual growth of 1.6%, but the overall level is low, and the overall spatial pattern of high in the north and low in the south is shown. The dominant type of urbanization is population and economic urbanization. (2) The average annual growth rate of net carbon emissions from land use in Ningxia is 4.75 106t/a. Spatially, it is characterized by higher cities in the north along the Yellow Ecological and Economic Zone, and lower in the central arid zone and southern mountainous areas. (3) The coupling degree and coupling coordination degree of urbanization and carbon emission of land use in Ningxia show a fluctuating upward trend, and the two are closely related but belong to mutual constraints at a low level. the government should take into account regional differences when formulating carbon emission reduction policies to maintain an appropriate population size, optimize economic structure, and improve land use efficiency.